The negligible effects of the antifungal natamycin on cholesterol-dipalmitoyl phosphatidylcholine monolayers may explain its low oral and topical toxicity for mammals - Arima, Anderson A. [UNESP]; Pavinatto, Felippe J.; Oliveira, Osvaldo N.; Gonzales, Eduardo R. P. [UNESP] (Elsevier B.V., 2014)
Natamycin is an effective, broad spectrum antifungal with no reported resistance, in contrast to most antimicrobials. It also exhibits reduced (oral and topical) toxicity to humans, which is probably associated with the lack of effects on mammalian cell membranes. In this paper we employ Langmuir monolayers to mimic a cell membrane, whose properties are interrogated with various techniques. We found that natamycin has negligible effects on Langmuir monolayers of dipalmitoyl phosphatidylcholine (DPPC), but it strongly affects cholesterol monolayers. Natamycin causes the surface pressure isotherm of a cholesterol monolayer to expand even at high surface pressures since it penetrates into the hydrophobic chains. It also reduces the compressibility modulus, probably because natamycin disturbs the organization of the cholesterol molecules, as inferred with polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS). In mixed cholesterol/DPPC monolayers, strong effects from natamycin were only observed when the cholesterol concentration was 50 mol% or higher, well above its concentration in a mammalian cell membrane. For a sterol concentration that mimics a real cell membrane in mammals, i.e. with 25 mol% of cholesterol, the effects were negligible, which may explain why natamycin has low toxicity when ingested and/or employed to treat superficial fungal infections. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Natamycin; Cholesterol; Dipalmitoyl phosphatidylcholine (DPPC); Langmuir films